2020
DOI: 10.3164/jcbn.20-11
|View full text |Cite
|
Sign up to set email alerts
|

<i>Dolichos lablab</i> L. extracts as pharmanutrient for stress-related mucosal disease in rat stomach

Abstract: Gastric stress-related mucosal disease (SRMD) presented from superficial gastritis to deep ulceration consequent to insufficient perfusion, ischemia, and oxidative stress. Though pharmacologic interventions to optimize tissue perfusion or to enhance defensive mechanism are essential, limited clinical outcome necessitates strong acid suppressors or natural agents. Under the hypothesis that Dolichos lablab L. (NKM 23-1) can enhance defense against SRMD, water immersion restraint stress (WI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 33 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…In clinic, the importance of either H. pylori eradication or their regulation impose significant impact on either gastric cancer prevention or gastric diseases amelioration, for which several kinds of intervention like natural products, probiotics, and more effective anti- H. pylori therapy are under active investigation. ( 68 71 ) In conclusion, walnut seems to be very effective and attractive because of well-acknowledgement as “pharmanutrient” against H. pylori infection. However, well-designed clinical trial should be followed.…”
Section: Discussionmentioning
confidence: 97%
“…In clinic, the importance of either H. pylori eradication or their regulation impose significant impact on either gastric cancer prevention or gastric diseases amelioration, for which several kinds of intervention like natural products, probiotics, and more effective anti- H. pylori therapy are under active investigation. ( 68 71 ) In conclusion, walnut seems to be very effective and attractive because of well-acknowledgement as “pharmanutrient” against H. pylori infection. However, well-designed clinical trial should be followed.…”
Section: Discussionmentioning
confidence: 97%
“…Corroborating this information, the main antioxidants such as SOD, CAT, HO-1, gamma-glutamylcysteine synthetase, and GSH-Px are regulated by Nrf-2 [109]. Thus, it is noteworthy that Nrf-2 mediated HO-1 induction has cytoprotective, anti-inflammatory, antioxidant, and anti-apoptotic activities providing a therapeutic target against SRMD [107].…”
Section: Immune Systemmentioning
confidence: 89%
“…In gastric injury, inflammatory cytokines IL-1β, IL-6, IL-8, IL-10, TNF-α, and the transcription factor NF-kB-p65 are present [70,71,94,106,107]. IL-1β and TNF-α are increased in ethanol-induced gastric ulcers [57].…”
Section: Immune Systemmentioning
confidence: 99%
“…Gastric mucins and mucus layers are secreted from superficial and glandular mucus-producing cells and central peptides are characterized as MUC5AC (synthesized by surface foveolate cells) and MUC6 (synthesized by cells from the neck and glands). After synthesis, mucin accumulates in the form of granules and is then secreted by exocytosis [ 36 , 37 ]. It has been reported that 75% of critically ill patients present evidence of altered mucus production within 24 hours of admission to the intensive care unit [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 75% of critically ill patients present evidence of altered mucus production within 24 hours of admission to the intensive care unit [38]. The loss of mucus-producing cells in the superficial epithelium after stress-induced gastric damage [37] and gastric I/R has been previously reported [39]. Following treatment with MT, the regeneration of AB-positive cells in the foveolar was observed, as well as an increase in the production of neutral glycosaminoglycans, suggesting that the treatment reversed the damage allowing these cell types to maintain barrier function.…”
Section: Plos Onementioning
confidence: 99%